Famílias que vivem na CEU/UFSM: crianças, mães e fragmentos de sua cotidianidade - Silva, Carolina Fontana da (2020)
This dissertation has as its theme the study of childhood and the production of children's cultures in everyday life based on the relationships established between children-young, children-adults and children-children. It aims to investigate the daily lives of children who live at the University Student Housing (Casa do Estudante Universitário - CEU) with their mothers, through dialogues, relationships, and movements, considering the cultures produced in this context, based on the following question: what stories about themselves and their everyday experiences do the children and their mothers who live in CEU tell us? Therefore, this work is linked to the Graduate Program in Education from the Federal University of Santa Maria (Universidade Federal de Santa Maria - UFSM), and to the research line LP2 – Educational public policies, educational practices and their interfaces. The methodology is qualitative, supported by cartography in education and by some aspects from ethnography, in addition, it is theoretically and methodologically based on bricolage, in which the record in the field diary, the photograph and the descriptive mapping of the territory were some of the techniques for data production. The research was carried out at CEU, located at UFSM, where visits were made, according to the availability of the families. In these visits, approximations between the researcher and the children were proposed, through conversations and games, in which dialogues were established. For the theoretical basis, we used authors such as Melucci (2004), Corsaro (2005; 2011; 2009), Oliveira and Paraíso (2012), Barros and Kastrup (2015), Heller (1970), Demause (1982), Del Priore (2016), among others. This research allowed us to analyze the student assistance service offered by UFSM, demonstrating the importance of valuing this public, free, and high-quality university, a reference in Brazil and in Latin America in student assistance. The families, constituted by the children and their mothers, told their stories, which, in a descriptive way, allowed us to build a map. The mothers told their stories like an outburst, they talked about their daily challenges, about the way they organized their routines or about the student assistance they received; while the children told their stories when they decided to invite the researcher to play and then constructed plots and dialogues, taking countless cultural elements to the play. Thus, mothers and children told their stories through the relationships established with others and with the researcher, through their smiles, hugs, and even through the negatives to visits and participation in the research. The stories, therefore, were told in the intricacies, between the lines and in the productions resulting from everyday life.